2013
DOI: 10.1179/2045772312y.0000000056
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized cardiovascular autonomic control and cognitive deficits in persons with spinal cord injury

Abstract: Summary: Spinal cord injury (SCI) results in motor and sensory impairments that can be identified with the American Spinal Injury Association (ASIA) Impairment Scale (AIS). Although, SCI may disrupt autonomic neural transmission, less is understood regarding the clinical impact of decentralized autonomic control. Cardiovascular regulation may be altered following SCI and the degree of impairment may or may not relate to the level of AIS injury classification. In general, persons with lesions above T1 present w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 91 publications
(110 reference statements)
0
31
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] The cause of the cognitive deficits in these patients is controversial because of potentially confounding factors, such as concurrent traumatic brain injury (TBI). However, cognitive changes after SCI in patients have been reported without a history or signs of TBI.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The cause of the cognitive deficits in these patients is controversial because of potentially confounding factors, such as concurrent traumatic brain injury (TBI). However, cognitive changes after SCI in patients have been reported without a history or signs of TBI.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been documented that chronic hypotension in persons with SCI is associated with deficits in memory and possibly attention and processing speed. 9,10 However, this issue has not been addressed experimentally with regard to mechanism. Only one prior experimental study has suggested cognitive decline after SCI-a projectile injury in pigs wearing body armor.…”
Section: Introductionmentioning
confidence: 99%
“…22,49 Our data support the notion that not only is MFV reduced in persons with SCI compared to AB controls, but SFV and DFV are also significantly lower. These findings indicate persistent cerebral hypoperfusion throughout the entire cardiac cycle in hypotensive individuals with chronic SCI, which may contribute to the increased incidence of cerebrovascular disease 50 and ischemic stroke, 18 as well as cognitive deficits, 23,51,52 and impairment in health related QOL. 10 …”
Section: Discussionmentioning
confidence: 87%